Development of Flat Shape Learning Media to Improve Children's Mathematical Understanding Using Macromedia Flash - Tonni Limbong; Zekson Arizona Matondang (JUKI : Jurnal Komputer dan Informatika, 2022)
Problems in learning that do not use media in the teaching and learning process and the low ability of children's mathematical understanding in learning flat shape material because there are not many media used for learning. This study aims to obtain the benefits of learning media for flat shapes using Macromedia Flash. This research method uses a research and development model. The development model used is MDLC (Multimedia Development Life Cycle), namely concept, design, material collecting, assembly, testing and distribution. In the field trial, the average pretest score was 68.24 while the posttest average score was 86.76. The average increase is 18.52. The minimum gain value is 0.62 while the maximum gain value is 1.00. In the distribution test the average pretest score is 60.33 while the posttest average score is 81.33. The average increase is 21. The minimum gain value is 0.77 while the maximum gain value is 0.83. Based on these data, the flat shape learning media using macromedia flash software can help improve students' understanding significantly in recognizing flat shapes.